Frankenstein’s Legacy: Utopian and Dystopian Visions in an AI-Driven World - Chaleila, Wisam Abughosh (Journal of Posthumanism, 2025)
The evolution of science fiction, from Asimov’s Robot series in the 1940s to films like T.I.M. (2024), has continually questioned the ethical boundaries of human creativity. Mary Shelley’s Frankenstein; or, The Modern Prometheus (1818) is one of the earliest works of science fiction that presents motifs resonating with modern artificial intelligence discourse predating contemporary discussions on AI by centuries. It particularly explores the creation of life and the consequences of scientific overreach. Situating Frankenstein within the broader continuum of science fiction, this article draws on literary theory, AI ethics, and speculative futures studies to examine the novel’s relevance that explicitly anticipates debates about utopian versus dystopian technological futures, illuminating the tensions between progress and peril. As AI technologies gradually blur the line between fiction and reality, the narratives under study become increasingly relevant, making this analysis, with Frankenstein at the forefront, a contribution to modern-day research on AI technologies.